Thermal induced shape‐memory and self‐healing of segmented polyurethane containing diselenide bonds. Issue 22 (13th February 2018) - Du, Weining; Jin, Yong; Pan, Jiezhou; Fan, Wuhou; Lai, Shuangquan; Sun, Xiaopeng
ABSTRACT: Herein, we synthesized a series of polyurethane copolymers (PUs) with poly(1, 4‐butylene adipate) glycol as soft segment and 2, 4‐toluene diisocyanate as well as extenders including 1, 4‐butanediol and di(1‐hydroxyethylene) diselenide as hard segment. The chemical structure, thermal property, crystallization behavior, shape memory, and self‐healing performances of the PUs were systematically characterized by a series of experiments. It was found that the PU2 containing a higher diselenide component (∼33 mol %) exhibited both shape memory and self‐healing behaviors under a moderate temperature (∼57 °C). Meanwhile, the PUs showed a good repeatability of shape memory function, and their fixity and recovery ratios were all above 90%. Additionally, the dynamic exchangeable feature of diselenide bonding endues the PUs chains with an acceptable reprocessability and self‐healing performances, and the PU2 sample could be healed for five times by thermal treatment with the healing efficiencies above 70%. This work provides a heuristic perspective for the development of shape memory and self‐healing materials. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46326. Abstract :